НАПРЯМИ ДЕРЖАВНОГО КОНТРОЛЮ ЗА ВИРОБНИЦТВОМ ТА ОБІГОМ СПИРТУ, АЛКОГОЛЬНИХ НАПОЇВ І ТЮТЮНОВИХ ВИРОБІВ - Больбіт, Юрій Леонідович (SUPREMANCE OF LAW, 2017)
The article, based on an analysis of scientific views of scholars and laws of Ukraine, the directions of state control over the production and circulation of alcohol, alcoholic beverages and tobacco products. Emphasized the complexity of the implementation of control activities for the production and circulation of alcohol, alcoholic beverages and tobacco products. However, it noted that the state legislatively sufficiently and clearly define areas of state control over the production and circulation of alcohol, alcoholic beverages and tobacco products
Keywords: directions; state control; production; circulation; alcohol; alcoholic beverages; tobacco products